Predicted Benign and Synonymous Variants in CYP11A1 Cause Primary Adrenal Insufficiency Through Missplicing - GÜRAN, TÜLAY (ENDOCRINE SOC, 2019)
Primary adrenal insufficiency (PAI) is a potentially life-threatening condition that can present with nonspecific features and can be difficult to diagnose. We undertook next generation sequencing in a cohort of children and young adults with PAI of unknown etiology from around the world and identified a heterozygous missense variant (rs6161, c.940G>A, p.Glu314Lys) in CYP11A1 in 19 individuals from 13 different families (allele frequency within undiagnosed PAI in our cohort, 0.102 vs 0.0026 in the Genome Aggregation Database; P < 0.0001). Seventeen individuals harbored a second heterozygous rare disruptive variant in CYP11A1 and two had very rare synonymous changes in trans (c.990G>A, Thr330 = ; c.1173C>T, Ser391 =). Although p. Glu314Lys is predicted to be benign and showed no loss-of-function in an Escherichia coli assay system, in silico and in vitro studies revealed that the rs6161/c.940G>A variant, plus the c.990G>A and c.1173C>T changes, affected splicing and that p. Glu314Lys produces a nonfunctional protein in mammalian cells. Taken together, these findings show that compound heterozygosity involving a relatively common and predicted benign variant in CYP11A1 is a major contributor to PAI of unknown etiology, especially in European populations. These observations have implications for personalized management and demonstrate how variants that might be overlooked in standard analyses can be pathogenic when combined with other very rare disruptive changes.
Keywords: Addison disease; silent variant; side chain cleavage enzyme; cytochrome p450scc; CYP11A1; CHAIN CLEAVAGE ENZYME; 46,XY SEX REVERSAL; CYTOCHROME P450SCC; MUTATIONS; GENE; PATIENT; HYPOSPADIAS